Pedagogical and Innovative Technologies as a Factor of Efficiency in Primary Education - Azizova Dilnoz Yuldashevna; Rasulova Sanobar Mamatqulovna (Genius Publishing Group, 2022)
This article at pedagogical and innovation Technologies is given as a factor of effectiveness in primary education. In addition, pedagogical technology is an innovative approach to the educational process.
Keywords: Innovation; pedagogical and innovative technologies; primary education